Mental health over the life course: Evidence for a U‐shape?. (13th October 2022) - Dijk, Hermien; Mierau, Jochen
Abstract: Mental health problems impose substantial individual and societal costs over the life‐cycle. The age‐profile of mental health problems is, however, not well understood. Hence, we study the age‐profile of mental health while introducing minimal bias to reach identification. Using mental health data from the United States Panel Study of Income Dynamics we apply first difference estimation to derive an unbiased estimate of the second derivative of the age effect as well as an estimate up to a linear period trend of the first derivative. Next, we use a battery of estimators with varying restrictions to approximate the first derivative. Our results suggest that the age profile of mental health in the US is not U‐shaped and we find tentative evidence that the age‐profile could follow an inverse U‐shape where individuals experience a mental health high during their life course. Further analyses, using German and Dutch data, confirm that these results do not only apply to the US, but also to Germany and the Netherlands.